IMPLEMENTASI PEMBANGUNAN PEDESTRIAN JALAN KHATIB SULAIMAN KOTA PADANG - Muthia Claudia Ulfa; Nora Eka Putri (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
The purpose of this study is to analyze the implementation of pedestrian improvement at khatib sulaiman street, Padang city and to identify the inhibiting factors of pedestrian improvement at khatib sulaiman street, Padang City. And to identify the inhibiting factors of pedestrian improvement at Khatib Sulaiman street, Padang city. pedestrian is an activity or human movement from one place to another by foot, or in other words, a pedestrian is a person walking on the street pedestrian network facilities and infrastructure generally function to facilitate the movement of pedestrian from one place to another easily, smoothly, safely, comfortably and independently. This research was a qualitative research which related to descriptive phenomena, events, social activities, techniques, interviews, and documentation. The data was analyzed throught data reduction and drawing conclusion. The results of this study indicated that there was not yet benefit showed related to the changes desired by government and society toward pedestrian. The factors that emerged on the performance, the existence of adequate pedestrian but lack of cummunicy awareness of using the facilities itself.